EXPERIMENTAL INVESTIGATION OF NANOPARTICLES FOR CANCER CARE AND APPLICATION IN BIOSENSING AND THERMAL ABLATION - Ashikbayeva, Zhannat (Nazarbayev University School of Engineering and Digital Sciences, 2022)
is related to the class of disorders characterized by abnormal cell proliferation that can spread and damage other human organs. There are diverse forms of cancer based on the position of a tumor in a human body. The most prevalent cancer types diagnosed in patients are breast, liver, lung, and prostate with high mortality rates worldwide. Surgery, chemotherapy, and thermal ablation (TA) therapy are known as conventional treatment techniques for the treatment of cancer. TA therapy is gaining interest in cancer cure due to its minimal invasiveness and ability to reach tumors in challenging regions to access. Moreover, not all patients surgical candidates because of medical and physical conditions. However, non-specific heat damage and non-accurate temperature monitoring are known as the main limitations during thermal therapy. Therefore, this thesis focused on the application of metallic nanoparticles during thermal procedures making it possible to rise the heat in the targeted region. Moreover, optical fibers may be employed as a sensing system temperature monitoring accurately in real time. In this work, the impact of metallic nanoparticles and metallic thin films is proposed, in order to improve cancer therapeutical and diagnostic tasks. On one side, the application of nanoparticles to cancer thermotherapies is discussed and quantitatively evaluated, in methods that employ radiofrequency, microwave, or optical power delivery methods. The heat increase during therapy was achieved and validated by several types of metallic nanoparticles, particularly iron oxide magnetic nanoparticles (IONPs), gold nanoparticles AuNPs), and silver nanoparticles (AgNPs). On the other hand, biosensors can improve the early-stage cancer diagnostic by detecting biomarkers for specific types of cancer; fiber optic sensors have shown detection at ultra-low limits, compatible with scarce analytes. Biosensors empowered by thin gold films or gold nanoparticles are discussed, showing how devices fabricated in-house can turn into highly performing devices through a functionalization step.
Keywords: type of access: embargo